IL-6 and diabetic kidney disease - Zhang, Lei; Xu, Futian; Hou, Liyan (Frontiers in Immunology, 2024)
Diabetic kidney disease (DKD) is a severe microvascular complication of diabetes associated with high mortality and disability rates. Inflammation has emerged as a key pathological mechanism in DKD, prompting interest in novel therapeutic approaches targeting inflammatory pathways. Interleukin-6 (IL-6), a well-established inflammatory cytokine known for mediating various inflammatory responses, has attracted great attention in the DKD field. Although multiple in vivo and in vitro studies highlight the potential of targeting IL-6 in DKD treatment, its exact roles in the disease remains unclear. This review presents the roles of IL-6 in the pathogenesis of DKD, including immunoinflammation, metabolism, hemodynamics, and ferroptosis. In addition, we summarize the current status of IL-6 inhibitors in DKD-related clinical trials and discuss the potential of targeting IL-6 for treating DKD in the clinic.